2021
DOI: 10.1038/s41598-021-98544-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic association of starvation-induced gene expression in head and neck cancer

Abstract: Autophagy-related genes (ARGs) have been implicated in the initiation and progression of malignant tumor promotion. To investigate the dynamics of expression of genes, including ARGs, head and neck squamous cell carcinoma (HNSCC) cells were placed under serum-free conditions to induce growth retardation and autophagy, and these starved cells were subjected to transcriptome analysis. Among the 21 starvation-induced genes (SIGs) located in the autophagy, cell proliferation, and survival signaling pathways, we id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 66 publications
2
9
0
Order By: Relevance
“…First, our independent analysis of the transcript expression levels of GRP78 in HNSCC, based on general as well as specific cancer subtypes, showed that GRP78 transcripts is uniformly elevated in the primary HNSCC tumors compared to normal tissues and that high transcript level of GRP78 is associated with poor prognosis. Our results validate previous studies that clinically, high GRP78 expression, at both protein and mRNA levels, is associated with worse patient survival ( 39 41 ). Utilizing two independent siRNAs targeting different regions of human GRP78 , we established that knockdown of GRP78 led to dramatic induction of CHOP, a UPR apoptotic marker in HNSCC, thus GRP78 integrity is a critical anti-apoptotic protein in HNSCC.…”
Section: Discussionsupporting
confidence: 91%
“…First, our independent analysis of the transcript expression levels of GRP78 in HNSCC, based on general as well as specific cancer subtypes, showed that GRP78 transcripts is uniformly elevated in the primary HNSCC tumors compared to normal tissues and that high transcript level of GRP78 is associated with poor prognosis. Our results validate previous studies that clinically, high GRP78 expression, at both protein and mRNA levels, is associated with worse patient survival ( 39 41 ). Utilizing two independent siRNAs targeting different regions of human GRP78 , we established that knockdown of GRP78 led to dramatic induction of CHOP, a UPR apoptotic marker in HNSCC, thus GRP78 integrity is a critical anti-apoptotic protein in HNSCC.…”
Section: Discussionsupporting
confidence: 91%
“…A GO analysis, KEGG pathway enrichment analysis, and construction of a PPI network have been used to identify key genes and pathways involved in carcinogenesis and cancer progression. 23,34 Geng et al reported that L6, STAT1, LYN, BDNF, C3,CD274, PDCD1LG2 and CXCL10 were important candidates associated with OSCC using bioinformatical analyses and attempted to demonstrate that P. gingivalis infection promoted the initiation and progression of OSCC. 35 In the present study, the GO analysis extracted 16 biological processes, including the ERK1/2 cascade, response to lipopolysaccharide, regulation of cell proliferation, and negative regulation of cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…Expression levels higher than the median were classified as the high expression group and the remainder as the low expression group. 23,28,29 The generalized Wilcoxon test and Log rank test were performed to assess the differences in survival times identified by the Kaplan-Meier method (Figures 3 and 4). Among the 12 up-regulated genes, the high expression of CCL20 (Figure 3A), HBEGF (Figure 3E), and PLAU (Figure 3I) correlated with shorter survival times, whereas the high expression of CTGF (Figure 3B), DUSP10 (Figure 3C), EGR3 (Figure 3D), IL1B (Figure 3F), IL24 (Figure 3G), JUN (Figure 3H), PTGS2 (Figure 3J), SEMA7A (Figure 3K) and SGK1 (Figure 3L) did not.…”
Section: Prognostic Significance Of 17 Genes Extracted From Migration...mentioning
confidence: 99%
See 1 more Smart Citation
“… 30 Like several cell models, in OSCC, using serum or nutrient starvation results in induction of autophagy. 30 , 31 Autophagy occurs in numerous stressful conditions, such as the presence of damaged proteins and organelles, nutrient deprivation and is a common phenomenon after cancer treatment. 9 , 10 Autophagy plays a paradoxical role in the promotion and suppression of tumours.…”
Section: Discussionmentioning
confidence: 99%